2006
DOI: 10.1016/j.jsgi.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-1 and -9 Promoter Polymorphisms and Endometrial Carcinoma Risk in a Japanese Population

Abstract: These results suggest that the MMP-9 -1562 C/T polymorphism may be associated with susceptibility to endometrioid carcinoma in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The C allele has been associated with a decreased risk of prostate cancer [13], and increased risks of squamous cell carcinoma of the lung [14], endometrial carcinoma [15], and colorectal cancer [16]. However, another study of prostate cancer found no association [17], as did two other studies for colorectal cancer [18,19], and one study of ovarian cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…The C allele has been associated with a decreased risk of prostate cancer [13], and increased risks of squamous cell carcinoma of the lung [14], endometrial carcinoma [15], and colorectal cancer [16]. However, another study of prostate cancer found no association [17], as did two other studies for colorectal cancer [18,19], and one study of ovarian cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a SNP in a regulatory region may have an influence on gene transcription, a SNP located in a RNA splice site may affect RNA splicing, a SNP in the 3'-untranslated region of a gene may have an effect on mRNA stability, and a SNP in the coding region may result in an amino acid substitution in the encoded protein. It is thought that SNPs contribute to interindividual variability in susceptibility to common diseases such as cancer [35,36]. So far, some published meta-analyses have confirmed that a number of SNPs are associated with increased or decreased PCa risk in different races, such as A49T in steroid-5-alpha-reductase, alpha polypeptide 2 (SRD5A2) gene [37], Gly388Arg in fibroblast growth factor receptor 4 (FGFR4) gene [38], -160C/A in E-cadherin (CDH1) gene [39], Val16Ala in manganese superoxide dismutase (MnSOD) gene [40], C677T in 5,10-methylenetetrahydrofolate reductase (MTHFR) gene [41].…”
Section: Discussionmentioning
confidence: 99%
“…Another Japanese study (endometrial cancer cases n = 107, controls n = 213) reported a nonsignificant decreased allele frequency in cases versus controls (64% versus 70%, χ 2 P = 0.13; ref. 50). This same study (50) investigated another SNP MMP9 −1562C > T (rs3918242), which is predicted to result in a loss of a repressor protein binding site.…”
Section: Mmp and Timp Expression In Endometrial Cancermentioning
confidence: 99%